Impact of Delays on Business Start-Up: A Case Study of SC and ST Women Entrepreneurs in Mysuru Division - Nikhilavathi S; Bharath V (Journal of International Business, Economics and Entrepreneurship)
This research considers the various factors contributing to delays in the initiation of businesses by SC and ST women entrepreneurs in Mysuru Division. The objectives are identified and analyse the factors causing delays in the start-up of businesses by SC and ST women entrepreneurs and develop a regression model that effectively predicts the delay in the initiation of businesses based on various predictors. Descriptive statistics, reliability analysis, and regression modelling were employed to analyse primary data collected from 514 respondents. The study identified various factors contributing to delays in the initiation of businesses by SC and ST women entrepreneurs in Mysuru Division. Key factors include shortages of raw materials, high costs, legal disputes, administrative hurdles, and difficulties in arranging finance. However, the study also presents a comprehensive model that effectively explains the delay phenomenon. The implications of these delays are discussed, emphasizing the need for targeted interventions to support women entrepreneurs.